A Common Fixed Point Theorem for Single-Valued and Set-Valued Mappings Satisfying A Generalized Contractive Condition: Abdelkrim Aliouche, Ahcene Djoudi - Team, Support (Thai Journal of Mathematics, 2010)
In this paper, we prove a common fixed point theorem for two pairs of single-valued and set-valued mappings satisfying a generalized contractive condition and a property using the concept of weak compatibility in metric spaces which generalizes Theorem 1 of [1] and Corollary 3 of [2].